1998
DOI: 10.1074/jbc.273.6.3117
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modification of PML by the Sentrin Family of Ubiquitin-like Proteins

Abstract: PML, a RING finger protein with tumor suppressor activity, has been implicated in the pathogenesis of acute promyelocytic leukemia that arises following a reciprocal chromosomal translocation that fuses the PML gene with the retinoic acid receptor ␣ (RAR␣) gene. Immunocytochemical analysis has demonstrated that PML is co-localized with a novel ubiquitin-like protein in the nuclear bodies, which could be disrupted by the PML-RAR␣ fusion protein. The physical nature of this co-localization is unknown. Using a CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
154
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 18 publications
9
154
0
1
Order By: Relevance
“…These are called PML nuclear bodies because the sumolated PML (promonocytic leukemia) protein was identified as a major component of these structures (55)(56)(57). We also observed that, unlike unmodified c-Myb, the sumolated Myb protein was insoluble in a Nonidet P-40-based lysis buffer, suggesting that conjugation of SUMO-1 may target c-Myb to detergent-resistant structures similar to PML nuclear bodies.…”
mentioning
confidence: 61%
“…These are called PML nuclear bodies because the sumolated PML (promonocytic leukemia) protein was identified as a major component of these structures (55)(56)(57). We also observed that, unlike unmodified c-Myb, the sumolated Myb protein was insoluble in a Nonidet P-40-based lysis buffer, suggesting that conjugation of SUMO-1 may target c-Myb to detergent-resistant structures similar to PML nuclear bodies.…”
mentioning
confidence: 61%
“…A number of SUMO-1-modified proteins localize in discrete structures in the nucleus including PML, HIPK2, and Sp100 (15)(16)(17)(18)(19). Therefore, to determine whether there is a relationship between HSF1 and SUMO-1 in stress-induced nuclear granules, we performed double labeled immunofluorescence analysis on normal and heat-treated HeLa cells using antibodies that recognize each of these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular fractionation experiments in mammalian cells showed that proteins that can form conjugates with SUMO are limited and are mostly high molecular weight nuclear proteins (7,8,25). Confirmed substrates include RanGAP1 (7,8,20,22), PML (9,26,27), Cdc3 (28), and IB␣ (29). Since none of the conserved lysine residues imperative for ubiquitin polymer formation are present in SUMO, SUMO is probably not able to form polymeric chains.…”
mentioning
confidence: 99%